PENGARUH RISIKO BISNIS DAN UKURAN PERUSAHAAN TERHADAP RETURN ON ASSET DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MODERASI (Studi pada Perusahaan Asuransi yang terdaftar di Bursa Efek Indonesia Periode 2015-2018) - Permana, Edi; Agustina, Yumniati (Kompartemen : Jurnal Ilmiah Akuntansi, 2021)
This research was conducted to determine the extent of the influence of business risk and firm size on return on assets with capital structure as a moderating variable. This study using a population of insurance companies listed on the Indonesia Stock Exchange (IDX). The sampling technique used is purposive sampling. Data analysis on this research uses multiple linear regression analysis, moderation regression analysis, t-test, f and coefficient of determination test. The results of this study indicate that business risk has a positive effect, while company size does not have a significant effect on return on assets. In addition, the capital structure is not able to moderate the effect of business risk and company size on the insurance company's return on assets. The results of the simultaneous study of business risk and company size have a significant influence on the return on assets.